Analisis Strategi Optimalisasi Penghimpunan Dana Zakat, Infak, dan Sedekah pada Lembaga Amil Zakat Solopeduli 2022 - Fitriyah Fitriyah; Supawi Pawenang; Raisa Aribatul Hamidah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The realization of zakat collection in Indonesia has experienced quite a large gap compared to the existing zakat potential. This happens because the zakat institution is less than optimal in implementing the strategy of collecting zakat, infaq, and sadaqa. This certainly creates a challenge for zakat institutions or organizations in maximizing their performance to take part in helping the government in efforts to minimize poverty in Indonesia. LAZ Solopeduli as a provincial-level LAZ with the best ZIS collection growth at the 2019 BAZNAS Award, of course, has a strategy and targets for collecting ZIS as an effort to maximize the potential of existing zakat. The purpose of this study was to find out the optimization strategies and constraints involved in compiling ZIS LAZ Solopeduli 2022. A descriptive-qualitative approach with a type of field research was used. Researchers used various data collection techniques including interviews with seven LAZ Solopeduli employees, observation, and documentation. The analysis was carried out in three stages, namely data reduction, data presentation and conclusion drawing, and verification. The data's credibility was tested using triangulation of data collection techniques. The results showed that the strategy for optimizing ZIS collection was carried out in three stages of strategy formulation, implementation, and evaluation. The formulation is prepared by setting annual targets, determining sources of funds, plotting targets, and formulating strategies. The collection is carried out using two direct and indirect fundraising methods. The strategies used are dialogue fundraising, corporate fundraising, multichannel fundraising, also donor retention and development. The constraints experienced stem from internal problems (limitations of human resources and lack of action) and external problems (government regulations and social issues). Keywords: Strategy Optimization, Fundraising, ZIS